Activation of a GPCR, ORL1 Receptor: A Novel Therapy to Prevent Heart Failure Progression - Saliha S. Pathan; Aarthi Pugazenthi; Beverly R. E. A. Dixon; Theodore G. Wensel; Todd K. Rosengart; Megumi Mathison (Journal of Cardiovascular Development and Disease)
The number of ischemic heart failure (HF) patients is growing dramatically worldwide. However, there are at present no preventive treatments for HF. Our previous study showed that Gata4 overexpression improved cardiac function after myocardial infarction in rat hearts. We also found that Gata4 overexpression significantly increased the expression of a Pnoc gene, an endogenous ligand for the cell membrane receptor ORL1. We hypothesized that the activation of the ORL1 receptor would suppress HF in a rat ischemic heart model. Adult Sprague Dawley rats (8 weeks old, six males and six females) underwent left anterior descending coronary artery ligation. Three weeks later, normal saline or MCOPPB (ORL1 activator, 2.5 mg/kg/day) intraperitoneal injection was started, and continued 5 days a week for 3 months. Echocardiography was performed six times: pre-operative, 3 days after coronary artery ligation, pre-MCOPPB or saline injection, and 1, 2, and 3 months after saline or MCOPPB injection started. Animals were euthanized after 3 months’ follow-up and the hearts were harvested for histological analysis. The ORL1 activator, MCOPPB, significantly improved cardiac function after myocardial infarction in rats (ejection fraction, MCOPPB vs. saline at euthanasia, 67 ± 3% vs. 43 ± 2%, p < 0.001). MCOPPB also decreased fibrosis and induced angiogenesis. Thus, the ORL1 activator, MCOPPB, may be a novel treatment for preventing HF progression.